2010
DOI: 10.1007/s11325-010-0425-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of positive airway pressure on cardiac status and clinical outcomes in patients with advanced heart failure and sleep-disordered breathing: a preliminary report

Abstract: In this preliminary study, we found that treatment of SDB, irrespective of type, in stable patients with advanced HF receiving optimal medical therapy was associated with improvement in cardiac functional status, ventricular contraction, physical performance, and neurohormonal status, leading to better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…[8,20,[32][33][34][35]. These findings are also confirmed by this study which revealed a significant decrease in PASP, a reduction in RV, right atrial, and inferior vena canal diameters, along with a reduction in RV wall thickness and a significant increase in TAPSE and RV tissue E/A ratio.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[8,20,[32][33][34][35]. These findings are also confirmed by this study which revealed a significant decrease in PASP, a reduction in RV, right atrial, and inferior vena canal diameters, along with a reduction in RV wall thickness and a significant increase in TAPSE and RV tissue E/A ratio.…”
Section: Discussionsupporting
confidence: 87%
“…A minority of patients with this disorder are diagnosed with the disease, and even a lower proportion of the affected patients is treated. Given the detrimental effects of OSA on the cardiovascular system, its early diagnosis and treatment are considered of paramount importance [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Observational data suggest that positive airway pressure therapy improves cardiac parameters [12][13][14] and is a significant independent predictor of survival in patients with chronic HF [11]. Adaptive servo-ventilation (ASV) is a positive pressure ventilator support system to normalize ventilation in patients with CSA-CSR [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ASV treatment improves cardiac function in CHF patients. [5][6][7][8][9] Although ASV therapy has beneficial effects on CHF, the intervention is frequently rejected by CHF patients because of unpleasant feelings from the mask or positive airway pressure (PAP). It remains unknown which patient characteristics influence the smooth introduction of ASV therapy.…”
mentioning
confidence: 99%